Low cell-matrix adhesion reveals two subtypes of human pluripotent stem cells - Yu, Leqian; Li, Junjun; Hong, Jiayin; Takashima, Yasuhiro; Fujimoto, Nanae; Nakajima, Minako; Yamamoto, Akihisa; Dong, Xiaofeng; Dang, Yujiao; Hou, Yu; Yang, Wei; Minami, Itsunari; et al. (Stem cell reports, 2018)
We show that a human pluripotent stem cell (hPSC) population cultured on a low-adhesion substrate developed two hPSC subtypes with different colony morphologies: flat and domed. Notably, the dome-like cells showed higher active proliferation capacity and increased several pluripotent genes’ expression compared with the flat monolayer cells. We further demonstrated that cell-matrix adhesion mediates the interaction between cell morphology and expression of KLF4 and KLF5 through a serum response factor (SRF)-based regulatory double loop. Our results provide a mechanistic view on the coupling among adhesion, stem cell morphology, and pluripotency, shedding light on the critical role of cell-matrix adhesion in the induction and maintenance of hPSC.